2012
DOI: 10.1007/s10484-012-9202-5
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback Assisted Control of Respiratory Sinus Arrhythmia as a Biobehavioral Intervention for Depressive Symptoms in Patients After Cardiac Surgery: A Preliminary Study

Abstract: The current study investigated whether biofeedback training aimed at increasing respiratory sinus arrhythmia (RSA), a measure of cardiac vagal modulation, can reduce depressive symptoms in patients after cardiac surgery. This randomized controlled study enrolled 26 patients after first-time cardiac surgery. The patients were randomly assigned to an RSA-biofeedback group (N = 13) or to a treatment as usual group (N = 13). The biofeedback training consisted of five 45 min sessions designed to increase RSA. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…This center communicates directly with the amygdala, a center for emotional control, in a pathway extending through the insula (Volz et al, 1990; Henderson et al, 2004). Perhaps it is for this reason that various studies have shown positive HRV biofeedback effects for treating anxiety and depression (Karavidas et al, 2007; Reiner, 2008; Siepmann et al, 2008; McCraty et al, 2009; Nada, 2009; Zucker et al, 2009; Henriques et al, 2011; Tan et al, 2011; Patron et al, 2013). …”
Section: The Baroreflexmentioning
confidence: 99%
See 1 more Smart Citation
“…This center communicates directly with the amygdala, a center for emotional control, in a pathway extending through the insula (Volz et al, 1990; Henderson et al, 2004). Perhaps it is for this reason that various studies have shown positive HRV biofeedback effects for treating anxiety and depression (Karavidas et al, 2007; Reiner, 2008; Siepmann et al, 2008; McCraty et al, 2009; Nada, 2009; Zucker et al, 2009; Henriques et al, 2011; Tan et al, 2011; Patron et al, 2013). …”
Section: The Baroreflexmentioning
confidence: 99%
“…Several studies have reported that HRVB might be effective in reducing symptoms of depression and/or anxiety (Karavidas et al, 2007; Reiner, 2008; Siepmann et al, 2008; McCraty et al, 2009; Nada, 2009; Zucker et al, 2009; Henriques et al, 2011; Tan et al, 2011; Patron et al, 2013). These results led to speculation that some other mechanism might be at work beyond the baroreflex gains.…”
Section: The Vagal Afferent Pathwaymentioning
confidence: 99%
“…For example, two studies found that biofeedback increased RSA and reduced depressive symptoms in individuals with PTSD (Zucker, Samuelson, Muench, Greenberg, & Gevirtz, 2009) and in a group of post-cardiac surgery patients (Patron et al, 2012). Vagus nerve stimulation has also been proposed as a treatment for chronic, treatment-resistant depression.…”
Section: Implications For Research and Treatmentmentioning
confidence: 99%
“…Recent studies have also highlighted the effectiveness of biofeedback training aimed at increasing respiratory sinus arrhythmia (RSA), a measure of cardiac vagal modulation, in reducing autonomic nervous system dysregulation, by increasing cardiac vagal tone and baroreflex gain both in patients with cardiovascular diseases and healthy adults (Del Pozo et al 2004;Lehrer et al 2003;Nolan et al 2005;Patron et al 2013).…”
Section: Introductionmentioning
confidence: 99%